Wheelchair Tai Chi Ball Exercise for Improving Neuromuscular Functions of Older Adults With Disability - Liao, Ting; Ke, Xiong-Wen; Wang, Yong Tai (Frontiers in Aging Neuroscience, 2022)
The purposes of this perspective article are to summarize Wheelchair or Seating Tai Chi studies related to neuromuscular functions of older adults with disability; to describe the development of Wheelchair Tai Chi Ball (WTCB) exercise --- a concept to combine mind-body exercise with strength training; and to propose a new Telehealth Wheelchair Tai Chi Ball exercise for improving neuromuscular functions of old adults with spinal cord injury and disability. To improve neuromuscular functions, Wheelchair Tai Chi intervention may have positive effects on simple reaction time, range of motion at the shoulder and trunk, static and dynamic sitting balance, handgrip strength, vagal activity and sympathetic activity among older adults with disability. Whereas, the WTCB intervention is a feasible and safe exercise which combines the mind-body exercise and strength conditioning into one exercise which possesses aerobic, stretching and strength training and may facilitate neuromuscular functions of older adults with disability. The proposed Telehealth Wheelchair Tai Chi Ball (TWTCB) with a “Moving Shadow” method in the telehealth that enables the learner to superimpose learner’s image on an expert’s demonstrating model to enhance the learning and practice effects. We speculate that the Wheelchair Tai Chi Ball movements are relatively stationary, since the wheelchair users will learn and practice while sitting on a wheelchair so that “Moving shadow” on Zoom would provide an ideal telehealth learning environment for wheelchair users to learn and practice Tai Chi Ball exercise from home effectively and efficiently.